Analysis of IEEE 802.15.4-Based Delay and Slot Duration Adjustment Combination Methods on Wireless Sensor Networks - Fitria Nisa Andari; Eppy Yundra; Nur Kholis; Arif Widodo; Farid Baskoro (Department of Electrical Engineering, Faculty of Engineering, Universitas Negeri Surabaya, 2021)
IEEE 802.15.4 is one of the standards of the Wireless Sensor Network (WSN) which is at the Medium Access Control (MAC) layer. IEEE 802.15.4 is also technology and protocol within a computer network that can connect all device quickly, has a large capacity and low power consumption. The challenge of Wireless Sensor Network is how to improve the Wireless Sensor Network network performance matrix (goodput, bandwidth utilization, and energy consumption) both in the Contention Access Period (CAP) and in the Contention Free Period (CFP) based on the IEEE 802.15.4 standard. This research is an analysis combination of adjustment delay and slot duration methods to increase goodput, bandwidth utilization and reduce energy consumption in Wireless Sensor Networks in the allocation guaranteed time slots on fixed data simulated using Castalia Simulator software. The problem of this research is whether the combination method can improve the performance matrix of Wireless Sensor Networks on fixed data compared to other methods (SUDAS, ADES, IEEE 802.15.4 Standard). This reserch it aims to determine the performance matrix of combination methods is when compared to other methods (Superframe Duration Adjustment Scheme (SUDAS), Adjustment Delay Scheme (ADES), IEEE 802.15.4 standard) using quantitative approach research methods. Based on the data obtained, the goodput of the combined method increased by 10%, 416%, and 513% respectively compared to the SUDAS method, ADES method, and IEEE 802.15.4 standards. Bandwidth utilization of the combination methods increased by 0.025, 0.223 and 0.232, respectively compared to the SUDAS method, the ADES method, and the IEEE 802.15.4 standard. And the consumption of the combination methods are respectively reduced by 1.02%, 8.72% and 9.08% compared to the SUDAS, ADES and IEEE 802.15.4 standards. With the combination method of delay adjustment and slot duration it is able to optimize the performance of the Wireless Sensor Network compared to other methods.